Innovative anti-proliferative effect of the antiviral favipiravir against MCF-7 breast cancer cells using green nanoemulsion and eco-friendly assessment tools - Eman Abd-Elrasheed; Sally A. Fahim; Christine K. Nessim; Sara Nageeb El-Helaly (Scientific Reports)
Abstract Telomerase enzyme prevents telomere shortening during division, having human telomerase reverse transcriptase (hTERT) as its catalytic subunit. Favipiravir (FAV), an RNA-dependent RNA polymerases inhibitor, shared structural similarity with hTERT and thus assumed to have cytotoxic effect on cancer cells, in addition to its prophylactic effect to immunocompromised cancer patients. Nanoemulsion (NE) is a potential tumor cells targeting delivery system, thereby enhancing therapeutic efficacy at the intended site, mitigating systemic toxicity, and overcoming multidrug resistance. The objective of this study is to develop a green FAV nanoemulsion (FNE) that is environmentally friendly and safe for patients, while aiming to enhance its cytotoxic effects. The study also highlights the environmental sustainability of the developed RP-HPLC method and assesses its greenness impact. The FNE formulation underwent thermodynamic stability testing and invitro characterization. Greenness was assessed using advanced selected tools like the Analytical Eco-Scale (AES), Analytical Greenness Metric for Sample Preparation (AGREEprep), and green analytical procedure index (GAPI). The cytotoxic potential of FNE was screened against MCF-7 breast cancer and Vero normal cell lines using SRB assay. Stable and ecofriendly FNE was formulated having a particle size (PS) of 25.29 ± 0.57 nm and a zeta potential of -6.79 ± 5.52 mV. The cytotoxic effect of FNE on MCF-7 cells was more potent than FAV with lower IC50 while FNE showed non-toxic effect on VERO normal cell line. Therefore, the FAV nanoemulsion formulation showed targeted cytotoxicity on MCF-7 cells while being non-toxic on normal Vero cells.